Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Fertilité naturelle, reproduction forcée - Tabet, Paola (L'Arraisonnement des femmes: essais en anthropologie des sexes, 1985)
Arraisonner quelqu'un, c’est en vieux français tenter de le persuader, argumenter pour lui faire entendre raison. En termes de marine et de police sanitaire, arraisonner un navire, c'est l'interpeller, interrompre sa route pour le contrôler. Ainsi, c'est de la double face, matérielle et mentale, du contrôle et de la manipulation des femmes que traite ce livre collectif. Par l'analyse de sociétés très diverses, anciennes et modernes, comme par la critique des discours scientifiques, les auteurs — ethnologues, sociologues, linguistes – éclairent avec rigueur et imagination théoriques deux domaines encore peu explorés de la problématique des sexes : 1) L’élaboration sociale (politique) de la sexualité et la manipulation des mécanismes de la reproduction — dont l'exposé dément les explications naturalistes ; 2) Les conditions socio-sexuées de la connaissance, les effets sur la conscience de l’oppression matérielle subie et exercée — dont l'analyse exclut toute explication idéaliste. Si les deux sexes sont socialement construits, ce n'est pas de façon symétrique. Objets de raisonnements réducteurs et réduites dans leur corps et dans leur raison, soumises à persuasion ou raisonnées de force, inspectées, contrôlées dans leur tête et dans leur ventre tel un navire sa cargaison, son état sanitaire, son port d'attache : ainsi sont-elles créées « femmes » dans de multiples sociétés. Ainsi s'exerce l'arraisonnement des femmes.
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; justice reproductive; justice sociale; maternité; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sexualité; soc1016; sociologie; systèmes d'oppressions; thématiques

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie